Emergency department management of patients with adult congenital heart disease: a consensus paper from the ESC Working Group on Adult Congenital Heart Disease, the European Society for Emergency Medicine (EUSEM), the European Association for Cardio-Thoracic Surgery (EACTS), and the Association for Acute Cardiovascular Care (ACVC). (21st May 2021) - Chessa, Massimo; Brida, Margarita; Gatzoulis, Michael A; Diller, Gerhard-Paul; Roos-Hesselink, Jolien W; Dimopoulos, Konstantinos; Behringer, Wilhelm; Möckel, Martin; Giamberti, Alessandro; Galletti, Lorenzo; Price, Susana; Baumgartner, Helmut; et al.
Abstract: Adult congenital heart disease (ACHD) patients represent a growing population with increasing use of acute emergency department (ED) care. Providing comprehensive ED care necessitates an understanding of the most common clinical scenarios to improve morbidity and mortality in this population. The aim of this position document is to provide a consensus regarding the management of the most common clinical scenarios of ACHD patients presenting to the ED. Graphical Abstract: